2010
DOI: 10.18553/jmcp.2010.16.1.32
|View full text |Cite
|
Sign up to set email alerts
|

Economic Evaluation of Childhood 7-Valent Pneumococcal Conjugate Vaccination in Korea

Abstract: BACKGROUND: Streptococcus pneumoniae (sp) is a leading cause of invasive and noninvasive bacterial disease in children. 7-valent pneumococcal conjugate vaccine (PCV-7) has been shown to significantly reduce the incidence of pneumococcal diseases, such as meningitis, bacteremia, pneumonia, and otitis media. Although PCV-7 was introduced in Korea in 2003, it is not yet included in the universal immunization program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 46 publications
(85 reference statements)
1
33
1
1
Order By: Relevance
“…All studies were based on (cohort-based) decision analysis models; some used a decision tree [21,[25][26][27][30][31][32] and others the slightly more complex Markov models. [7,15,16,18,20,[22][23][24]28,29,33,34] Table II lists the selected studies and their general Excluded records (n = 5)…”
Section: Search Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…All studies were based on (cohort-based) decision analysis models; some used a decision tree [21,[25][26][27][30][31][32] and others the slightly more complex Markov models. [7,15,16,18,20,[22][23][24]28,29,33,34] Table II lists the selected studies and their general Excluded records (n = 5)…”
Section: Search Resultsmentioning
confidence: 99%
“…Twelve studies were performed in eight European countries, [15][16][17][18]20,21,[25][26][27]29,30,34] five in North America, [7,23,24,28,33] two in South America [22,32] and one each in Australia [19] and Asia. [31] All but one study reported on the cost effectiveness of PCV7. This one study concerned a combined 9-valent pneumococcal and meningococcal B vaccine.…”
Section: Search Resultsmentioning
confidence: 99%
See 3 more Smart Citations